The environmentalist movement in the world and environmental studies in the marketing literature - Bilge Nur Öztürk (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2021)
Problems such as environmental pollution, the depletion of the ozone layer, the melting of glaciers due to global warming, the decline in clean resources and the extinction of some species have prompted people to consider the idea of a more sustainable world. In this process, humanity is going through a mental transformation and gaining some awareness. As emphasized in this study, all crises (accidents, fi res, outbreaks, etc.) experienced worldwide have been the driving forces for environmental transformations. Environmentalist movements emerging from this orientation have also found their place in the world of science and therefore in the marketing literature. From this point of view, the aim of this study is to explain the scientifi c publications inspired by the environmental transformations experienced chronologically and to reveal the part that is present in the marketing literature. In this study, it has been shown with which intensity environmental studies have been included in the marketing literature. In addition, it was determined which marketing journals were discussed intensely. This study points to potential academic fi elds of study. Finally, this study emphasizes that while trying to explain green consumer profi les, attention should be paid to macro factors (lifestyle, sociological variables, etc.) in addition to micro factors such as values and norms. National and corporate green policies can be more successful if handled in this context.
Keywords: M30; M31; 650; environmental studies; green marketing; sustainability; green consumption